2022
DOI: 10.7759/cureus.32487
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Severe COVID-19 Patients Following Percutaneous Versus Open Surgical Tracheostomy: An Analysis of Clinical and Prognostic Indicators

Abstract: Background and objectiveTracheostomy in coronavirus disease 2019 patients can be performed in cases of prolonged intubation or in patients with a known difficult airway. Tracheostomy is usually performed by two main approaches: open surgery or percutaneous endoscopic insertion. However, few studies have compared these two techniques in severe COVID-19 patients. The objective of the present study was to compare the efficacy of the two main methods of tracheostomy among patients with severe COVID-19 infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Furthermore, the SOFA score was higher with statistically significant differences in patients taken to open tracheostomy. However, a retrospective observational study involving 72 patients reported a mortality rate of 92% in patients who underwent open tracheostomy compared to 65.9% in the percutaneous tracheostomy group in patients with Sars-Cov2 infection [ 12 ], suggesting that the technique employed may influence mortality, as evidenced in the results of this study.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Furthermore, the SOFA score was higher with statistically significant differences in patients taken to open tracheostomy. However, a retrospective observational study involving 72 patients reported a mortality rate of 92% in patients who underwent open tracheostomy compared to 65.9% in the percutaneous tracheostomy group in patients with Sars-Cov2 infection [ 12 ], suggesting that the technique employed may influence mortality, as evidenced in the results of this study.…”
Section: Discussionmentioning
confidence: 81%
“…Surgical techniques for tracheostomy are open and percutaneous, with contradictory reports about the preferred choice [ 12 14 ]. This paper aims to describe the clinical results and complications after tracheostomy in patients with COVID-19, according to both surgical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), caused by the novel coronavirus, has rapidly caused a global health crisis. Coronavirus disease 2019 (COVID-19) clinical manifestations range from asymptomatic individuals to respiratory arrest needing mechanical ventilation, with a significant death and morbidity rate, especially in the elderly [1]. In the pathophysiology of COVID-19 infection, the angiotensinconverting-enzyme receptor 2 (ACE2) plays a critical role [2].…”
Section: Introductionmentioning
confidence: 99%
“…The novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) has further dramatically impacted all areas of healthcare, and it is especially evident across critical care settings with a significant increase in the incidence of tracheostomy (Akbari et al, 2022;Singh et al, 2022;Vuu et al, 2022;Williams & McGrath, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The novel severe acute respiratory syndrome coronavirus (SARS‐CoV‐2) has further dramatically impacted all areas of healthcare, and it is especially evident across critical care settings with a significant increase in the incidence of tracheostomy (Akbari et al, 2022; Singh et al, 2022; Vuu et al, 2022; Williams & McGrath, 2021). Unfortunately, the emergence of the virus has created a high‐risk tracheostomy patient care environment where healthcare providers are at an elevated risk for viral infections through droplets and aerosolized secretions (McGrath, Brenner, et al, 2020;Meister et al, 2021; Pandian et al, 2020; Zaga et al, 2020).…”
Section: Introductionmentioning
confidence: 99%